Lipid Processing in the Brain: A Key Regulator of Systemic Metabolism - Bruce, Kimberley D.; Zsombok, Andrea; Eckel, Robert H. (Frontiers in Endocrinology, 2017)
Metabolic disorders, particularly aberrations in lipid homeostasis, such as obesity, type 2 diabetes mellitus (T2D), and hypertriglyceridemia often manifest together as the Metabolic Syndrome (MetS). Despite major advances in our understanding of the pathogenesis of these disorders, the prevalence of the MetS continues to rise. It is becoming increasingly apparent that intermediary metabolism within the central nervous system (CNS) is a major contributor to the regulation of systemic metabolism. In particular, lipid metabolism within the brain is tightly regulated to maintain neuronal structure and function, and may signal-nutrient status to modulate metabolism in key peripheral tissues such as the liver. There is now a growing body of evidence to suggest that fatty acid-sensing in hypothalamic neurons via accumulation of fatty acids (FA) or FA metabolites may signal nutritional sufficiency and may decrease hepatic glucose production, lipogenesis and VLDL-TG secretion. In addition, recent studies have highlighted the existence of liver-related neurons that have the potential to direct such signals through parasympathetic and sympathetic nervous system activity. However, to date whether these liver-related neurons are FA-sensitive remain to be determined. The findings discussed in this review underscore the importance of the autonomic nervous system in the regulation of systemic metabolism, and highlight the need for further research to determine the key features of FA-neurons, which may serve as novel therapeutic targets for the treatment of metabolic disorders.